Perlindungan Hukum Bagi Para Pihak dalam Kegiatan Equity-Based Crowdfunding di Indonesia - Ni Gusti Agung Ayu Putu Rismajayanti; Anak Agung Gede Duwira Hadi Santosa (University of Udayana, 2022)
Equity crowdfunding investors need legal certainty and legal protection for their investments. On the other hand, equity issuers and platform operators also need to get legal certainty from the Financial Services Authority. The Financial Services Authority has issued Financial Services Authority Regulation (POJK) Number 37/POJK.04/2018 regarding Funding Services through Information Technology Based Shares (Equity Crowdfunding). The problem examined in this paper is how the construction of legal relations and legal protection for the parties in equity crowdfunding in Indonesia. This study uses a normative method by reviewing the laws and regulations related to the legal issues studied. The results of the study concluded that the parties in holding equity crowdfunding, namely share issuers, organizers, and investors, all three has a triangular relationship that is born based on agreements or laws and regulations. Even though the OJK has issued regulations relating to equity crowdfunding, the current regulations do not guarantee full legal protection especially for investors. Penerbit equity serta penyelenggara platform juga perlu mendapatkan kepastian hukum dari Otoritas Jasa Keuangan. Otoritas Jasa Keuangan telah menerbitkan Peraturan Otoritas Jasa Keuangan (POJK) Nomor 37/POJK.04/2018 tentang Layanan Urun Dana Melalui Penawaran Saham Berbasis Teknologi Informasi (Equity Crowdfunding). Permasalahan yang dikaji dalam penulisan ini adalah bagaimana konstruksi hubungan hukum serta perlindungan hukum bagi para pihak dalam equity crowdfunding di Indonesia. Penelitian ini menggunakan metode normatif dengan mengkaji peraturan perundang-undangan terkait permasalahan hukum yang diteliti. Hasil penelitian menyimpulkan bahwa para pihak dalam penyelenggaraan equity crowdfunding, yaitu penerbit saham, penyelenggara, dan pemodal, ketiganya memiliki hubungan hukum yang lahir berdasarkan perjanjian maupun peraturan perundang-undangan. Meskipun OJK telah menerbitkan peraturan terkait equity crowdfunding, pengaturan yang ada saat ini belum memberikan jaminan perlindungan hukum sepenuhnya khususnya bagi pemodal.